Composition Operator, Boundedness, Compactness, Hyperbolic Bloch-Type Space βμ∗, Hyperbolic-Type Space - Shuan Tang; Pengcheng Wu (Journal of Function Spaces)
In this paper, we obtain some characterizations of composition operators Cφ, which are induced by an analytic self-map φ of the unit disk Δ, from hyperbolic Bloch type space βμ∗ into hyperbolic type space QK,p,q∗.